Kontribusi Bank Syariah Terhadap Pemberdayaan Ekonomi Umat : Perspektif Fiqh Muamalat - Ladaina, Muhammad satria; Taufikurrahman, Muhammad; Azwari, Peny Cahaya (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2024)
This study examines the contribution of Islamic banks to economic empowerment from the perspective of fiqh muamalah. The research aims to explore the strategic role of Islamic banks in transforming community economics through a comprehensive literature analysis. The research method uses a qualitative approach with a systematic literature review of 15 international journals from 2019-2024. The research results show that Islamic banks have a multidimensional contribution to economic empowerment, covering technological, social, environmental, and ethical aspects. Financial technology innovations, green banking practices, and Islamic financial instruments are identified as the primary empowerment mechanisms. The fiqh muamalah perspective provides a normative framework that integrates principles of justice, transparency, and social welfare in economic practice. The study concludes that Islamic banks have the potential to become sustainable socio-economic transformation agents, transcending conventional intermediation functions.